Study on Effect of Light Intensity and Perch on Welfare and Some Behavioral Traits in Broilers - Okur, EZ; Fidan, ED (Journal of the Hellenic Veterinary Medical Society, 2024)
The present study examined the effect of light intensity and perch use of broilers on welfare status (foodpad dermatitis (FPD), hock burn (HB), gait score (GS), eye dimensions) and some behavioral traits (standing, sitting, walking, feeding, drinking, leg extension, lying down, trimming their feathers, pecking, wing and flapping, aggressive behavior and perching) in broilers. A total of 270, 1-day age male broiler chicks were randomly assigned to groups based on the light intensity (5, 20, and 80 lux) and perch use (perch and no perch) with three replicates. No footpad dermatitis was found in the light intensity and perch groups. 20 and 80 lux light intensity tended (P<0.01) to decrease the incidence and severity of HB lesions. There was no effect of perch use on the GS of broiler chickens. Eye weight was determined to be lowest (2.019 g) in the 80 lux light intensity group and highest (2.107 g) in the 5 lux group (P<0.05). In the study, it was observed that the presence of the perch reduced the walking and standing behaviors statistically (P<0.001). It was observed that the use of 20 lux light intensity in broilers both reduced incidence of HB and reduced eye weight, positively affecting the welfare of broilers. In conclusion, these results suggest that perch use have a beneficial effect on the walking, standing, and wing flapping behaviors of chickens.